Adaptive filter-FLC integration for torque ripples minimization in PMSM using PSO - Yasser Ahmed; Ayman Hoballah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
The article presents torque and flux ripples minimization based on adaptive filter. The adaptive filter coefficients optimized and adapted on line by using particle swarm optimization (PSO) technique. The proposed methodology applied on closed loop speed control based on direct torque control (DTC) for surface mounted permanent magnet synchronous motor (PMSM). Fuzzy logic controller (FLC) used as speed controller while proportional-integral (PI) controller used as torque and flux controllers. Second order infinite impulse response (IIR) filter is used for ripple reduction generated due to FLC. The drive system modeled using Matlab/Simulink software in order to dynamically evaluate the performance of the proposed drive system at different operating conditions. The results provide evidence that the adaptive filter-FLC integration with optimal coefficients minimizes torque and flux ripples with reduction of total harmonic distortion generated in the three-phase currents.